2019
DOI: 10.3389/fmars.2019.00453
|View full text |Cite|
|
Sign up to set email alerts
|

Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian

Abstract: Responses of cnidarian-Symbiodiniaceae associations to warming are determined, in part, by high-frequency temperature variability. Yet, the role of such variability in determining specific maximum temperature thresholds of cnidarian holobionts (the ecological units comprised of cnidarian hosts and associated microorganisms, including Symbiodiniaceae) remains untested. Here we contrasted the thermal resilience (that is the ability to resist stress) of a model symbiotic cnidarian from the Red Sea (jellyfish of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 67 publications
5
42
1
Order By: Relevance
“…Coupled with the effects of heat stress, NO 3 − may thus further destabilize symbiotic nutrient cycling in corals. Likewise, previous studies showed that symbiotic cnidarians from areas with strong diurnal temperature variations are more thermotolerant than their counterparts in areas of low temperature variability (41,71,72). Here we found that heat stress stimulates both respiration as well as photosynthesis rates.…”
Section: Symbiotic Nutrient Cycling Explains Patterns Of Bleaching On Coralsupporting
confidence: 84%
See 1 more Smart Citation
“…Coupled with the effects of heat stress, NO 3 − may thus further destabilize symbiotic nutrient cycling in corals. Likewise, previous studies showed that symbiotic cnidarians from areas with strong diurnal temperature variations are more thermotolerant than their counterparts in areas of low temperature variability (41,71,72). Here we found that heat stress stimulates both respiration as well as photosynthesis rates.…”
Section: Symbiotic Nutrient Cycling Explains Patterns Of Bleaching On Coralsupporting
confidence: 84%
“…Consequently, the observed depletion of host energy reserves during heat stress is likely more pronounced at night in the absence of photosynthesis. As diurnal temperature variability commonly involves a cooling at night and warming during the day ( 72 ), this implies that strong diurnal temperature variations will reduce the effects of heat stress on the energy budget of the host compared to areas with similar mean temperature but lower diurnal variability. Hence, high diurnal temperature variations may stabilize symbiotic nutrient cycling during heat stress.…”
Section: Resultsmentioning
confidence: 99%
“…For example, regions of higher mixing and temporal thermal respite have be found to result in lower mortality in benthic invertebrates and habitat‐forming organisms (Baird et al, ; Frade et al, ; Green et al, ; Richards et al, ; Roberts et al, ). These examples support the assertion that regions characterized by high thermal variance, and those with short‐term respite during extremes, have greater capacity to withstand extreme conditions (Ainsworth et al, ; Castillo, Ries, Weiss, & Lima, ; Klein et al, ; Morikawa & Palumbi, ; Page et al, ).…”
Section: What Can We Learn From Recent Climate Extremes?supporting
confidence: 61%
“…At the end of the experiment, the oral arms (in their entirety) were cut into smaller sections and stored at −20 • C for chlorophyll a content, total protein, and Symbiodiniaceae density analyses (LaJeunesse et al, 2018) following a protocol adapted from Klein et al (2016Klein et al ( , 2019. Marginal appendages and vesicles were included in the analyses.…”
Section: Traits Measuredmentioning
confidence: 99%